A comparative study of oral health amongst trisomy 21 children living in Riyadh, Saudi Arabia: Part 1 caries, malocclusion, trauma - M. AlSarheed (Elsevier, 2015)
Background: Trisomy 21 (T21) is a genetic disorder stemming from a chromosomal abnormality and characterized by general and mental retardation. Depending on the population, T21 is known to affect 1 in every 600-2000 live births. The current literature provides a mixed view on the oral health status of T21 individuals. Aim: To establish the prevalence of dental caries, malocclusion, and trauma amongst children with T21 compared with non-T21 children in Riyadh, Saudi Arabia. Methods: This cross-sectional study recruited non-T21 and T21 children between the ages of 7-15 years who were studying at the Saut Society. After informed consent was obtained from parents and both groups were matched by age and gender, trained examiners screened children at the dental clinic of King Saud University to record the presence of dental caries, malocclusion, and trauma in both groups. Results: While there was no statistical difference between the two groups with regard to the mean decayed, missing, and filled teeth (DMFT) index (2.66 for T21 versus 3.11 for controls), T21 children had a higher prevalence of incisal fractures compared to the control group (24.73% versus 4.95%, respectively) and that was statistically significant (P < 0.05). There were also highly significant group differences concerning the prevalence of malocclusion. Therein, 45% of T21 children had a Class III incisor relationship compared with 8% of control children, and 50% of T21 children had a Class III molar relationship compared with 8% of control children. Conclusions: While there was no significant difference in the incidence of caries between children with and without T21, practitioners should be aware of the disparities in malocclusion and trauma in this vulnerable population. Keywords: DownSyndrome, Caries, Malocclusion, Trauma